Strength training in team handball - Kvorning, T. (5th International Conference on Strength Training, Oktober 2006, 2006)
Team handball is a complex sport and players may be successful in spite of different profiles in terms of technical, tactical, psychological and physical characteristics. However, the finest purpose of physical conditioning is to insure that the physical parameters are not the limiting factor to success. Then again, the degree of success of physical conditioning of handball players relies on the design of the strength training programs and thus the carry-over effect from the fitness room to the playing pitch. However, a perfectly designed strength training program may loose its effect in increasing physical performance parameters if the athletes do not train optimal. For that reason supervision and motivation of the athletes during strength training is of paramount importance. The training load needs to fit the individual athlete and he/she must constantly be motivated to progress in training loads. Additional training (e.g. ball training and playing drills, aerobic and anaerobic training) should always be taken in to consideration in the planning of training cycles. For that reason are communication between the head coach and the physical conditioning coach vital and the outcome may be further individualization of the strength training to insure optimal gains. In addition, when physiotherapists are involved in the rehabilitation of the athletes a close dialog between the physiotherapists and physical conditioning coach is also crucial. Finally, the importance of proper nutrition and restitution can not be neglected and the counseling of athletes on this matter needs high priority.